2021
DOI: 10.1021/acsfoodscitech.0c00069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Lactobacillus zeae against Enterotoxigenic Escherichia coli F4 Infection in an In Vitro Porcine Intestinal Epithelial Cell Model

Abstract: Lactobacillus zeae (LB1 strain) has been shown to prevent the death of Caenorhabditis elegans caused by enterotoxigenic Escherichia coli (ETEC) infection by downregulating the gene expression of ETEC toxins and mediating antimicrobial peptides/defense molecules under the p38 mitogen-activated protein kinase (MAPK) and insulin/insulin-like growth factor (DAF/IGF) signaling pathways in the nematode. However, the protective effects of L. zeae LB1 at cellular and molecular levels have not yet been investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…Thus, B. licheniformis PF9 could be a promising alternative to antibiotics. This observation is consistent with a previous study described by Chen et al. (2021) , which may in part be explained by enhanced gut barrier function with increased mRNA expression of the tight junction proteins ZO-1 and OCLN in the jejunum detected in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, B. licheniformis PF9 could be a promising alternative to antibiotics. This observation is consistent with a previous study described by Chen et al. (2021) , which may in part be explained by enhanced gut barrier function with increased mRNA expression of the tight junction proteins ZO-1 and OCLN in the jejunum detected in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Those short-chain fatty acids are considered a useful energy source utilized by pigs to develop the large intestine ( den Besten et al, 2013 ). Recent studies have identified the protective effect of Bacillus strains on intestinal cells challenged with enteric pathogenic bacteria, since they found the pre-treatment of Bacillus could upregulate tight junction protein expression and decrease quorum sensing ( Chen et al, 2021 ; Li et al, 2022a , 2022 b). For weaned piglets, including lactic acid-producing bacteria in their dies could relieve weaning stress, reduce diarrhea, and enhance growth performance ( Yang et al, 2015a , 2015b ).…”
Section: Using Probiotics To Improve Gut Healthmentioning
confidence: 99%
“…L. chiayiensis was first isolated in 2018 from cow manure (Huang et al, 2018), and since then, this species has not been reported anymore. L. zeae, designated as an independent species from L. casei in 2020, has been said to exhibit antimicrobial activity against two strains of enterotoxigenic Escherichia coli (Zhou et al, 2014;Huang et al, 2020;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%